The future Faculty of Architecture and Ekistics (FAE) - Suriatini Ismail; Ahmad Rasdan Ismail; Khairul Azhar Mat Daud; Nik Zulkarnaen Khidzir; Abu Hassan Hasbullah; Ab. Aziz Shuaib; Nuzul Haqimi Muhammad; Rosdi Abd Rahman (Universiti Malaysia Kelantan, 2014)
This paper outlines the basis of formation for the future Faculty of Architecture and Ekistics (FAE) at Universiti Malaysia Kelantan (UMK). Efforts put towards the establishment of the new faculty manifest the commitment by UMK to pursue its strategic plan to continue developing further through its current Faculty of Creative Technology and Heritage (FTKW). The new faculty will be the first in Malaysia to use the term “Ekistics” in its name. This will come together with the aspiration to address creative futurism. Two main fields under the umbrella of FAE will be Built Environment (BE) and Built Environment Management (BEM). These will serve as the main pillars of academic programmes and research activities in FAE. By emphasising on the scholarship of teaching, FAE will move towards a research focus faculty with heritage, entrepreneurial and technology being blended together to support its main areas which are architecture and ekistics.